In the opinion of elite volleyball coaches, how do contextual variables influence individual volleyball performance in competitions? - Lopéz-Serrano, C.; Moreno Arroyo, M. P.; Mon López, D.; Molina Martín, J. J. (Sports, 2022)
The main objective was to know the elite coaches` opinions regarding the relevance, definition, and importance of volleyball contextual variables to measure individual performance in competition. After performing a literature review, an instrument to gather the opinion of the world`s elite volleyball coaches was elaborated by four volleyball specialists. The sample of experts consisted in 20 world`s elite volleyball coaches who met at least three experience years in first division or national teams. The instrument collected experts` information on the contextual variables in relation to relevance, definition, and importance. Cronbach`s a and Aiken`s V coefficient were used to test the reliability and content validity of the contextual variables, respectively. To compare the importance of the contextual variables U de Mann-Whitney and Kruskal-Wallis tests were used. Results showed that opposition level, set period, score difference, results of the previous set, competitive load variables, high level, final periods =20, and high load categories were relevant (Aikens V > 0.70). In addition, high level, final period =20 and =+10, and high load categories were significantly more important (p < 0.05). We conclude that, according to the elite coaches, the contextual variables should not be analyzed separately. Future studies should consider contextual variables dynamically.